The Efficacy of Yeast Phagostimulant Baits in Attract-and-Kill Strategies Varies between Summer- and Winter-Morphs of Drosophila suzukii - Rory Jones; Paul E. Eady; Matthew R. Goddard; Michelle T. Fountain (Insects, 2022)
Drosophila suzukii (Matsumura), is a globally invasive pest of soft and stone fruit. To survive winter in temperate zones it enters a reproductive diapause in a morphologically distinct phenotype. Phagostimulant baits can be combined with insecticides in attract-and-kill strategies for control. We investigated the effectiveness of single yeast species and combinations of co-fermented yeast phagostimulant baits when combined with insecticides in laboratory assays against both summer- and winter-morph D. suzukii. Candida zemplininia or Hanseniaspora uvarum + C. zemplininia combined with lambda-cyhalothrin or cyantraniliprole, and H. uvarum combined with cyantraniliprole caused significantly higher mortality in winter- compared to summer-morph D. suzukii. Additionally, lambda-cyhalothrin combined with M. pulcherrima + H. uvarum resulted in greater mortality compared to single yeasts, H. uvarum for both summer- and winter-morphs and C. zemplininia for summer-morphs. M. pulcherrima + H. uvarum with spinosad significantly reduced the time-to-kill (50%) of summer-morphs compared to insecticide alone. Most yeast-based baits were comparable in terms of attract-and-kill efficacy to Combi-protec, a commercially available bait, although M. pulcherrima or H. uvarum + C. zemplininia in with cyantraniliprole were less effective. Our study suggests that yeast phagostimulants in attract-and-kill strategies should be adjusted for summer- and winter-morph D. suzukii for more effective control.